Meningkatkan Pendidikan Literasi Digital Berbasis Aplikasi Microsoft Word Di SMAN 1 Kecamatan Ukui Kabupaten Pelalawan Provinsi Riau - Fitri, Kurniawaty; Anwari, Irma; Fadhilah, Harum; Rahma, Fatia; Nurbela, Intan; Sundari, Sundari; Fata, Abiyu; Rizfi, Muhammad; Tabitha, Daffa; Rahmawati, Desi; Sadri, Nove (Yayasan Daarul Huda Kruengmane, 2024)
As information and communication technology develops, digital literacy education becomes more crucial. However, many students lack the basic skills to utilize digital technology efficiently and safely. The purpose of this study is to address the problem of digital literacy among students by using an action-oriented approach. The method of action was chosen because it allows active involvement of students in the learning process. The study was conducted in an upper secondary school with 12th grade students. This therapy consists of an introduction to the Microsoft Word application, an overview of its functions and how to correctly and accurately generate reports. This activity is expected to make students experience an increase in digital literacy knowledge and skills after the intervention. Not only that, students also showed improved critical thinking skills and better use of technology. In summary, the method of action is effective in addressing the problem of digital literacy and can be used as a model in various educational situations to improve digital literacy among students.